IMPLEMENTASI BERMAIN CONGKLAK UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ANAK RETARDASI MENTAL DI SLB NEGERI SLAWI - Anisa Oktiawati; Sherly Agustia Ningrum (Bhamada: Jurnal Ilmu dan Teknologi Kesehatan (E-Journal), 2025)
Bacground: Mental retardation is a lifelong mental disorder characterized by decreased intellectual function and limitations in behavior, speech, motor skills, self-care skills and difficulty in grasping lessons, one of which is counting. Playing congklak can be one way to stimulate the development of mentally retarded children to improve counting and motor skills. WHO, 2019 recorded 12% of people with mental retardation in the world and made it a burden in itself. Based on Central Java BPS data, there is an increase in the number of mental retardation camps reaching 4,808 people between 2016-2021. Objektive: Implementing playing congklak to improve counting skills in mentally retarded children. Methodology: This research is a descriptive analytical study with a case study approach. The research subjects consisted of 2 children with mental retardation who attended SLB Negeri Slawi. Data were collected through counting ability tests before and after the intervention, as well as through participatory observation and interviews with teachers and parents. Data were presented in the form of narrative text and tables. This research has gone through an ethical feasibility test with number 004/Univ.Bhamada/KEP.EC/V/2024. Result: Client 1's counting score before playing congklak was 7 and client 2 was 4, after being given therapy playing congklak for 3 days client 1's counting score became 10 and client 2 was 7 out of a total of 10 questions. In addition, observations showed that children were more enthusiastic and excited in learning to count through congklak games than conventional methods. Recommendation: This study recommends the use of congklak game as one of the fun and effective learning methods for children with special needs.